2004
DOI: 10.1534/genetics.104.034801
|View full text |Cite
|
Sign up to set email alerts
|

A 2600-Locus Chromosome Bin Map of Wheat Homoeologous Group 2 Reveals Interstitial Gene-Rich Islands and Colinearity With Rice

Abstract: The complex hexaploid wheat genome offers many challenges for genomics research. Expressed sequence tags facilitate the analysis of gene-coding regions and provide a rich source of molecular markers for mapping and comparison with model organisms. The objectives of this study were to construct a highdensity EST chromosome bin map of wheat homoeologous group 2 chromosomes to determine the distribution of ESTs, construct a consensus map of group 2 ESTs, investigate synteny, examine patterns of duplication, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 40 publications
2
48
0
1
Order By: Relevance
“…Recurrent origin of pericentromeric inversions: Previously Qi et al (2006) reported that pericentric regions in the Triticeae, especially those of group-4 chromosomes, have undergone rapid and recurrent rearrangements. Pericentromeric inversions close to the centromere regions were detected in wheat chromosomes 2B, 3B, 4A, 4B, 5A, and 6B, as well as in other Triticeae species (Conley et al 2004;Linkiewicz et al 2004, Miftahudin et al 2004Qi et al 2004Qi et al , 2006. Analyzing W7-R8 centromere homology, we observed two independent pericentromeric inversions involving chromosome 7R of rye and 7D of wheat (Figures 1b and 2).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Recurrent origin of pericentromeric inversions: Previously Qi et al (2006) reported that pericentric regions in the Triticeae, especially those of group-4 chromosomes, have undergone rapid and recurrent rearrangements. Pericentromeric inversions close to the centromere regions were detected in wheat chromosomes 2B, 3B, 4A, 4B, 5A, and 6B, as well as in other Triticeae species (Conley et al 2004;Linkiewicz et al 2004, Miftahudin et al 2004Qi et al 2004Qi et al , 2006. Analyzing W7-R8 centromere homology, we observed two independent pericentromeric inversions involving chromosome 7R of rye and 7D of wheat (Figures 1b and 2).…”
Section: Discussionmentioning
confidence: 74%
“…These ESTs are diagnostic markers detecting pericentric inversions in homologous groups 2, 3, 4, 5, and 6 in the Triticeae and are markers for the pericentromeric regions of wheat chromosomes (Conley et al 2004;Linkiewicz et al 2004;Miftahudin et al 2004;Qi et al 2004Qi et al , 2006. Two cDNA clones, PSR161 and BCD1072, were previously mapped to the centromere of chromosome 1B (Sandhu et al 2001;Francki et al 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wheat physical map was adapted from previously published maps (Sourdille et al 2004;Conley et al 2004). The rice physical map was adapted from the Rice Functional Genomics Database website (http://signal.salk.edu/cgi-bin/RiceGE).…”
Section: Genetic Markers Genetic Map and Physical Mapsmentioning
confidence: 99%
“…Sourdille et al (2004) mapped gwm374 to the proximal region of chromosome 2BS using wheat deletion lines (C-2BS1-0.53 bin) confirming our previous assignment of GPC-B2 to this centromeric bin. Conley et al (2004) further dissected the C-2BS1-0.53 centromeric bin into 3 consensus bins (designated CS, 1S and 2S from proximal to distal, Fig. 2) and mapped BF291736 and other wheat ESTs to CS, the most proximal bin (Fig.…”
Section: Gpc-b2 and Os07g37920 Are Located In Syntenic Wheat-rice Regmentioning
confidence: 99%